2018
DOI: 10.3390/ijms19040999
|View full text |Cite
|
Sign up to set email alerts
|

The Different Facets of Extracellular Calcium Sensors: Old and New Concepts in Calcium-Sensing Receptor Signalling and Pharmacology

Abstract: The current interest of the scientific community for research in the field of calcium sensing in general and on the calcium-sensing Receptor (CaR) in particular is demonstrated by the still increasing number of papers published on this topic. The extracellular calcium-sensing receptor is the best-known G-protein-coupled receptor (GPCR) able to sense external Ca2+ changes. Widely recognized as a fundamental player in systemic Ca2+ homeostasis, the CaR is ubiquitously expressed in the human body where it activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 322 publications
(391 reference statements)
1
16
0
Order By: Relevance
“…There are a wide range of ions that can act as a ligand for the CaSR and these can act together to activate the receptor and induce intracellular signaling. The CaSR responds to di-and tri-valent cations including Sr 2+ , Ba 2+ , Mg 2+ , Ba 2+ , Mn 2+ , Ni 2+ , Gd 3+ , La 3+ and Al 3+ [3,5]. While ions such as Ca 2+ and Mg 2+ act as activators, sulphates act as negative allosteric modulators as well as stabilizers for the active confirmation of the receptor [6].…”
Section: Casr Structure and Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a wide range of ions that can act as a ligand for the CaSR and these can act together to activate the receptor and induce intracellular signaling. The CaSR responds to di-and tri-valent cations including Sr 2+ , Ba 2+ , Mg 2+ , Ba 2+ , Mn 2+ , Ni 2+ , Gd 3+ , La 3+ and Al 3+ [3,5]. While ions such as Ca 2+ and Mg 2+ act as activators, sulphates act as negative allosteric modulators as well as stabilizers for the active confirmation of the receptor [6].…”
Section: Casr Structure and Regulationmentioning
confidence: 99%
“…CaSR is present in various organs and its exact function can differ based on its location. CaSR is not only activated by calcium ions, but by numerous ligands that including various cations, polyamines, polypeptides and antibiotics [3]. The combination of this wide variety of ligands triggers intricate intracellular signaling networks, which eventually influence many physiological and pathological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Upon reaching 60-70% confluency, the cells were washed once in DPBS and then stimulated. Since Ca 2+ /CaSR inhibit the cAMP response in healthy cells [54], the cells for this assay were stimulated with experimental buffers supplemented with forskolin (FSK). FSK is a potent activator of stimulatory G protein (Gs), and stimulates the maximum level of cAMP in the cells.…”
Section: Cyclic Adenosine Monophosphate (Camp) Elisa Assaymentioning
confidence: 99%
“…Qi et al reported that the activation of CaSR increases [Ca 2+ ] i and activates the mitochondrial pathway and mitogen-activated protein kinase (MAPK) pathway, leading to the apoptosis of cardiomyocytes . Actually, besides heart (Gerbino and Colella, 2018), CaSR has been detected in various tissues, such as the thyroid (Ding et al, 2013), kidney (Kwak et al, 2005), and liver (Xing et al, 2010). Therefore, CaSR may be crucial in leading to cholestasis-related hepatocyte apoptosis.…”
Section: Introductionmentioning
confidence: 99%